MODEL PEMBELAJARAN GUIDED DISCOVERY (GD) DISERTAI MEDIA AUDIOVISUAL DALAM PEMBELAJARAN IPA (FISIKA) DI SMP - Rahmi Dwi Ariyani; Indrawati Indrawati; I Ketut Mahardika (FKIP Universitas Jember, 2017)
This research focuses on the application of Guided Discovery learning modelwith Audiovisual media.The purpose of this research were: (1) to describe studentsscience process skill using guided discovery learning model with audiovisual mediain teaching science physics in junior high school and (2) to assess the influence ofguided discovery learning model with audiovisual media to the student’s sciencephysic achievement in junior high school. This type of research is an experimentalresearch by post test only control group design that held in SMPN 1 Sumbersuko,Lumajang in the odd semester of the 2016/2017 academic year. The technique ofdata collection were observation, documentation, interview and test. The data wereanalyzed by using descriptif technique and independent sample t-test from SPSS 26.The findings of this research were: (1) students science process skills by usingguided discovery model along with audiovisual media in science-physics study isclassified in good criteria; (2) guided discovery learning model with audiovisualmedia significantly influences to the student’s science-physic achievement in juniorhigh school.Key words: guided discovery learning model, audiovisual media, science processskill, achievement.